Right to Sue (Citizen Law Suit) Air Pollution as an Alternative Dispute Settlement - Ulfanora, Ulfanora (Nagari Law Review, 2024)
A good and healthy environment is a human right of every Indonesian citizen. The mandate of the 1945 Constitution is not obtained by citizens as they should. The proof is that high air pollution, such as air quality in some areas, causes environmental damage. As for the negative impact of air pollution, in addition to material losses, it also causes immaterial losses in poor air quality. Facing the occurrence of environmental damage due to air pollution in the city of Jakarta, citizens have the right to sue the government as state administrators who have neglected to protect the rights of their citizens, as regulated in Article 91 paragraph (1) and (2) of Law no. 32 of 2009. The results of this study are that the Citizen Lawsuit lawsuit becomes a forum for the community if they experience losses due to pollution and environmental damage. This Citizen Lawsuit lawsuit only asks for accountability for Government policies that result in losses for citizens, such as the lawsuit filed by the Optimistic Capital Coalition on Number 374/Pdt.G/2019/Pn.Jkt.Pst which was received by the Panel of Judges in 2021.